INTEGRATION OF PLAY-BASED ARABIC LANGUAGE LEARNING IN DEVELOPING EARLY CHILDHOOD LINGUISTIC COMPETENCE - Hanun, Aisyatul; M. Abdul Hamid; Mohammad Kholison; Aushofil Karimah; Tri Wahyu Martiningsih (Fakultas Tarbiyah Universitas Ibrahimy Situbondo, 2026)
This study aims to analyze and describe the integration of play-based Arabic language learning in developing early childhood linguistic competence. Early childhood education represents a critical period for language acquisition, where appropriate stimulation significantly influences children’s future language abilities. However, Arabic language instruction in early childhood settings often relies on conventional methods, such as rote memorization, which are less aligned with children’s developmental characteristics. Therefore, this study proposes a play-based learning approach as a more effective and child-centered alternative. This research employed a qualitative approach with a case study design conducted at Raudhatul Athfal Ibrahimy Sukorejo. The participants included teachers, the school principal, and children aged 5–6 years. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that play-based Arabic language learning is implemented through various activities such as songs, role-playing, storytelling, and the use of visual learning media. This approach creates a meaningful, interactive, and enjoyable learning environment that enhances children’s engagement. Furthermore, the results indicate that play-based learning contributes significantly to the development of linguistic competence, including phonological, morphological, syntactic, semantic, and pragmatic aspects. Children not only acquire vocabulary but also demonstrate the ability to use Arabic in simple communicative contexts. In conclusion, play-based Arabic language learning serves as an effective and holistic pedagogical model for early childhood education. It provides both theoretical and practical contributions to improving language teaching practices that are developmentally appropriate and contextually relevant.